On the plastic deformation accompanying cyclic martensitic transformation in thermomechanically loaded NiTi. (December 2018) - Heller, L.; Seiner, H.; Šittner, P.; Sedlák, P.; Tyc, O.; Kadeřávek, L.
Abstract: Cyclic thermomechanical loading tests were performed on a medical grade superelastic NiTi wire in wide temperature range −100 °C - +200 °C. It was observed, that plastic unrecoverable deformation occurs only when forward or reverse martensitic transformations proceed under external stress. Based on this, unrecovered strains generated separately by the forward and reverse martensitic transformations were evaluated using an originally proposed method and presented in a "3D unrecovered strain-stress-temperature diagram". It was found, that the unrecovered strains increase exponentially with increasing stress and temperature, at which the forward and reverse transformations occurred and that comparable or even larger unrecovered strains were generated by the reverse transition than by the forward one. Within the framework of continuum mechanics, a theoretical model of the coupling between martensitic transformation and plasticity was derived from the requirement for strain compatibility at propagating habit plane interfaces and/or stationary defects as grain boundaries or inclusions. The model qualitatively explains most of the presented experimental results, except of martensitic transformations proceeding under high temperature-high stress conditions. Graphical abstract: Highlights: Unrecovered strains generated only when forward and/or reverse martensitic transformations proceed under external stress. Unrecovered strains generated by the forward and reverse transformations separately presented in a 3D unrecovered strain-stress-temperature diagram. Unrecovered strains generated by the forward and reverse transformation are comparable and increase exponentially with increasing temperature. A theoretical model of transformation - plasticity coupling in NiTi was developed within the framework of continuum mechanics. Convergent and cumulative mechanisms of transformation-plasticity coupling were introduced.